WDR62 Regulates Early Neural and Glial Progenitor Specification of Human Pluripotent Stem Cells. (13th June 2017) - Alshawaf, Abdullah J.; Antonic, Ana; Skafidas, Efstratios; Ng, Dominic Chi-Hung; Dottori, Mirella
Abstract : Mutations in WD40-repeat protein 62 ( WDR62 ) are commonly associated with primary microcephaly and other developmental cortical malformations. We used human pluripotent stem cells (hPSC) to examine WDR62 function during human neural differentiation and model early stages of human corticogenesis. Neurospheres lacking WDR62 expression showed decreased expression of intermediate progenitor marker, TBR2, and also glial marker, S100 β . In contrast, inhibition of c-Jun N-terminal kinase (JNK) signalling during hPSC neural differentiation induced upregulation of WDR62 with a corresponding increase in neural and glial progenitor markers, PAX6 and EAAT1, respectively. These findings may signify a role of WDR62 in specifying intermediate neural and glial progenitors during human pluripotent stem cell differentiation.